Інтеграція ШІ в транспортну систему України - Сандулов, Євген Генадійович (Ірпінь, 2026)
Робота полягає в розкритті теоретичних і практичних аспектів інтеграції ШІ в транспортну систему Украіни. Охарактеризувати SMART-мету проєкту; здійснити аналіз внутрішнього та зовнішнього середовища проєкту; надати оцінку сильних та слабких сторін проєкту; охарактеризувати особливості планування реалізації проєкту; дослідити особливості планування тривалості проєкту; охарактеризувати норми планування ресурсів та бюджету проєкту; провести моніторінг ефективності реалізації проєкту; здійснити управління ризиками проєкту; охарактеризувати особливості управління рекламною компанією проєкту;

The study explores the theoretical and practical aspects of integrating artificial intelligence into Ukraine’s transport system within the context of digital transformation and smart city development. The SMART objectives of the project are defined. An analysis of the project’s internal and external environment is conducted, and its strengths and weaknesses are assessed. The specific features of project implementation planning are characterized, including the planning of project duration, resources, and budget. The effectiveness of project implementation is monitored, and project risk management is carried out. Particular attention is given to the management of the project’s communication and promotional campaign.
Keywords: інноваційні проєкти; цифрова трансформація; штучний інтелект; «розумне» місто; транспортна система; innovative projects; digital transformation; artificial intelligence; and the smart city